LITERATUR REVIEW KARAKTERISTIK SISWA SEKOLAH DASAR DAN IMPLIKASI TERHADAP PEMBELAJARAN - Mirnawati, Liana; Irawan, Dadang; Kamilah, Siti khafidatul; Nengsih, Luluk Wahyu (Sindoro: Cendikia Pendidikan, 2024)
This research aims to determine the literature review of the characteristics of elementary school students and the implications for learning. This research uses a descriptive qualitative approach. The research results show that education in the form of elementary school level characteristics also has an important role as an initial form of developing characteristics for students during their development period. The literature review in research is in the form of characteristics of elementary school students and implications for learning where learning consists of several elements that interact with each other: teachers, students, objectives, materials, media, methods, and assessment.